El Crédito de Desarrollo Humano y su incidencia en la reducción de la pobreza de los beneficiarios de la Parroquia de Columbe, periodo 2015 – 2017. - Guambo Alcocer, Luis Alfredo (2019)
In the present degree work, a study was carried out on “The Human Development Credit and its incidence in the reduction of the poverty of the beneficiaries of the columbe Parish, period 2015 – 2017”, that allowed to have a real knowledge about the productive influence that this program has within the research population. In the introduction, we explain about the origins of the Human Development Credit in the country, through a brief explanation and its evolution to what this program means today, detailing the problem, problematization and hypothesis. State of the art begins with the existing background of this research, to arise established concepts by various authors who theoretically base each of the research variables. In The methodology, the type, techniques and research instruments essential for the present development are established, defining the population and sample object of study to which a survey is applied to obtain timely information on which our research is based. In the final section, we concluded through a critical analysis of the information obtained to determine the compliance of the variables.